From predator to protector: Myxococcus fulvus WCH05 emerges as a potent biocontrol agent for fire blight - Han, Jian; Dong, Zhiming; Ji, Wenbo; Lv, Wen; Luo, Ming; Fu, Benzhong (Frontiers in Microbiology, 2024)
Fire blight, caused by the Gram-negative bacterium Erwinia amylovora, poses a substantial threat to pome fruit production worldwide. Despite existing control strategies, a pressing need remains for sustainable and environmentally friendly fire blight management. Myxobacteria, renowned for their predatory behavior and potent enzymes, emerge as a groundbreaking biocontrol approach with significant potential. Here, we report the biocontrol potential of a novel Myxococcus fulvus WCH05, against E. amylovora. Using various in vitro and planta assays, we demonstrated the multifaceted biocontrol abilities of strain WCH05. In plate predation assays, strain WCH05 exhibited not only strong predation against E. amylovora but also broad-spectrum activities against other plant pathogenic bacteria. Pre-treatment with strain WCH05 significantly decreased pear blossom blight incidence in detached inflorescence assays, achieving a controlled efficacy of 76.02% that rivaled the antibiotic streptomycin (79.79%). In greenhouse trials, strain WCH05 effectively reduced the wilting rate and disease index in young pear seedlings, exhibiting both protective (73.68%) and curative (68.66%) control. Further investigation revealed that the biocontrol activity of strain WCH05 relies on both direct contact and extracellular enzyme secretion. While cell extracts lacked inhibitory activity, ammonium sulfate-precipitated secreted proteins displayed potent lytic activity against E. amylovora. Substrate spectrum analysis identified peptidases, lipases, and glycosidases among the secreted enzymes, suggesting their potential roles in pathogen degradation and biocontrol efficacy. This study presents the first evidence of Myxococcus fulvus WCH05 as a biocontrol agent against fire blight. Its potent predatory abilities and enzymatic arsenal highlight its potential for sustainable disease management in pome fruit production. Future research will focus on identifying and characterizing specific lytic enzymes and optimizing strain WCH05 application strategies for field efficacy.